Effect of different water levels on the growth and development of bulb onion (Allium cepa L.) - Alvarez-Herrera, Javier Giovanni; Alvarado-Sanabria, Oscar Humberto; Suesca-Ochoa, Freddy Alonso (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Because of the shallow root system of the onion plant, it requires irrigation at the proper time and intensity in order to promote the absorption of water and nutrients to obtain a high yield. We evaluated the irrigation rate effect on onion growth and development in a sandy loam soil with a sprinkler irrigation system. The experiment design was completely randomized with four treatments (evaporation coefficients of 0.8, 1.0, 1.2 and 1.4 of (Ev)), each with 16 repetitions, for 64 experiment units; each experiment unit was a 1 m2 plot. The 1.2 coefficient (43 L per plant per cycle) showed the highest total dry mass and dry mass of the bulb with significant differences from the 0.8 coefficient, but no differences with the application of the 1 and 1.4 Ev. Furthermore, the 1.2 Ev treatment showed the highest root dry mass. There was no significant difference between the treatments during the first 70 days after transplant, but after this time, there was a statistically difference and the 1.2 Ev showed the highest dry matter accumulation.